Effects of packaging and waxing on fruit quality and shelf life of some introduced mango cultivars - Elkashif, Mohamed E; Abdelfadil, Omiama E (Gezira Journal of Agricultural Science; Vol 14 No 1 (2016))
Mango is one of the most important fruit crops in the Sudan. It is annually exported to Saudi Arabia, Gulf States and Western Europe. Recently, some internationally popular cultivars have been introduced to the Sudan. The objective of this research was to determine the effects of packaging and waxing on postharvest fruit quality and shelf life of some introduced mango cultivars from South Africa. Treatments consisted of three introduced mango cultivars; Tommy Atkins, Kent and Keitt and the local cultivar Abusamaka. Packaging treatments consisted of intact polyethylene film, perforated film, waxing and control. Treatments were arranged in a completely randomized design with three replicates. Data taken consisted of weight loss, total soluble solids (TSS), titratable acidity (TA), vitamin C and shelf life. Results showed that Abusamaka cultivar had the highest weight loss and Keitt had the lowest in both seasons. Packaging mango fruits in intact polymeric film resulted in the lowest weight loss, followed by perforated film, waxing and the highest weight loss was recorded for the control in both seasons. Abusamaka cultivar had the highest vitamin C and TA contents but had the lowest TSS content. However, Tommy Atkins had the highest TSS content but the lowest vitamin C and TA contents in both seasons. The longest shelf life was shown by Keitt cultivar, followed by Kent, Abusamaka and the shortest shelf life was recorded for Tommy Atkins in both seasons. Packaging mango fruits in intact polymeric film resulted in the lowest TSS, the highest TA, the highest vitamin C content and the longest shelf life. However, the highest TSS, the lowest TA, the lowest vitamin C and the shortest shelf life were recorded for the control. It is recommended to grow Keitt cultivar, harvest fruits at the mature green stage and package them in intact polymeric film or waxed to increase their shelf life and improve their quality.               تعتبر المانجو من أهم محاصيل الفاكهة في السودان. وهي تصدر إلى المملكة العربية السعودية ودول الخليج وغرب أوروبا. لقد تم استقدام بعض الأصناف المرغوبة عالمياً إلى السودان في السنوات الأخيرة. الهدف من هذه الدراسة هو معرفة تأثير التغليف والتشميع على نوعية الثمار وفترة الصلاحية لثمار بعض أصناف المانجو المستجلبة من جنوب أفريقيا. اشتملت المعاملات على ثلاثة أصناف مستجلبة من المانجو وهي تومي أتكنز وكنت وكيت بالإضافة إلى الصنف المحلي أبو سمكة. معاملات التغليف شملت تغليف الثمار في أكياس البولي إثلين السليمة أو المخرمة أو تشميع الثمار وأخرى استخدمت كشاهد بدون كيس أو تشميع. أستخدم التصميم العشوائي الكامل بثلاثة مكررات. اشتملت البيانات على فقدان الوزن والمواد الصلبة الذائبة والحموضة المعايرة وفيتامين ج وفترة الصلاحية. أظهرت النتائج أن الصنف أبو سمكة أظهر أعلى معدل فقدان للوزن بينما الصنف كيت كان له أقل فقدان للوزن في كلا الموسمين. تغليف ثمار المانجو في أكياس البولي إثلين السليمة أعطى أقل فقدان للوزن ويليه الأكياس المخرمة ثم التشميع وكان أعلى فقدان للوزن في الثمار غير المغلفة أو المشمعة في كلا الموسمين. الصنف أبو سمكة أعطى أعلى محتوى لفيتامين ج والحموضة بينما أعطى أقل محتوى للمواد الصلبة الذائبة. الصنف تومي أتكنز أعطى أعلى محتوى للمواد الصلبة الذائبة ولكنه أعطى أدنى محتوى من فيتامين ج والحموضة في كلا الموسمين. الصنف كيت أعطى أطول فترة للصلاحية، يليه  كنت ثم أبو سمكة وأقل فترة للصلاحية كانت للصنف تومي أتكنز في كلا الموسمين. تغليف ثمار المانجو في أكياس البولي إثلين السليمة أعطى أدنى محتوى من المواد الصلبة الذائبة وأعلى محتوى من الحموضة وفيتامين ج وأطول فترة للصلاحية. أما الثمار غير المغلفة أو غير المشمعة أعطت أعلى محتوى من المواد الصلبة الذائبة وأدنى محتوى من الحموضة وفيتامين ج وأقصر فترة للصلاحية. يوصى بإكثار وزراعة الصنف كيت وحصاد الثمار في طور النضج الاخضر وتغليفها في أكياس البولي إثلين السليمة لإطالة فترة صلاحيتها وتحسين نوعيتها.